Mechanism of crack initiation under high cycle fatigue through an EBSD based approach in a 10 wt% Cr steel - Sarkar, A.; Yadav, S.D.; Nagesha, A.; Mariappan, K.; Ramaseshan, S. (Elsevier Ltd, 2020)
The study presents an insight into the mechanism of crack initiation under high cycle fatigue (HCF) and estimation of the initiation life thereof, using electron backscatter diffraction (EBSD) as an important tool in a 10% Cr ferritic steel. The localized plastic deformation facilitating crack initiation under HCF is found to be associated with dislocation multiplication and localized cyclic hardening. This process is found to occur concomitantly with the substructural development through the localized deformation leading to formation of new subgrains which act as barriers to the dislocation motion. The subgrain strengthening that arises as a consequence, adds to the local internal stress through dislocation pile-ups, aiding the process of crack initiation. The local internal stress is computed using the average subgrain size, which in turn is used to estimate the critical length required for the crack to self-propagate under the applied HCF stress, applying the principle of fracture mechanics. This concept is also utilized to identify the crack propagation threshold demarcating the regimes of propagating and non-propagating cracks. © 2020
Keywords: HCF; Fatigue crack; EBSD; Dislocations; 10 wt % Cr-steel